Through Hell and High Water: A Librarian’s Autoethnography of Community Resilience after Hurricane Katrina - Beth Patin (MediaTropes, 2016)
This autoethnographic essay presents a critical reflection on personal experiences of the process of rebuilding and working in a library in the Lower Ninth Ward in New Orleans, Louisiana following Hurricane Katrina. I examine meaningful moments during this process in the context of information science and community resiliency. The framework of community resilience is used to help structure the reflection and analysis in a systematic way. I share examples of the adaptive capacities of the school library as evidence of how the community adjusted to demonstrate resiliency.